Prevalence of and Risk Factors for Intimate Partner Violence in the First 6 Months Following HIV Diagnosis Among a Population‑Based Sample in Rural Uganda - Ogbonnaya, Ijeoma N.; Wanyenze, Rhoda K.; Reed, Elizabeth; Silverman, Jay G.; Kiene, Susan M. (AIDS and behavior, 2020)
Research in Uganda examining HIV-positive status disclosure and IPV victimization is scarce, and existing findings may not generalize to community-based samples of men and women newly diagnosed with HIV in Uganda. We investigated the prevalence of lifetime IPV, IPV experienced between HIV diagnosis and 6 months following diagnosis (recent IPV), and IPV specifically related to a partner learning one’s HIV-positive status among a sample of men and women newly diagnosed with HIV in a population-based study in rural Uganda. We also examined correlates of recent IPV, including HIV-positive status disclosure. The sample included 337 participants followed for 6 months after HIV diagnosis. Lifetime IPV findings showed that over half of the sample reported experiencing emotional IPV (62.81% of men, 70.37% of women), followed by physical IPV (21.49% of men, 26.39% of women) then sexual IPV (7.44% of men, 17.59% of women). For recent IPV, men and women reported similar rates of physical (4.63% and 8.29%, respectively) and emotional (19.44% and 25.91%, respectively) IPV. Women were more likely than men to report recent sexual IPV (8.29% vs. 1.85%); however, this relationship was no longer significant after controlling for other risk factors associated with sexual IPV (AOR = 3.47, 95% CI [0.65, 18.42]). Participants who disclosed their HIV-positive status to their partner had 59% lower odds of reporting emotional IPV (AOR = 0.41, 95% CI [0.21, 0.81]) than participants who did not disclose their HIV-positive status. Younger age, non-polygamous marriage, lower social support, and greater acceptance for violence against women were also significantly associated with experience of recent IPV. Overall, 12.20% of participants who experienced recent IPV reported that the IPV was related to their partner learning their HIV-positive status. Findings highlight the need for IPV screening and intervention integrated into HIV diagnosis, care, and treatment services.
Keywords: Intimate partner violence; Domestic violence; Gender-based violence; HIV-status disclosure; HIV; Uganda; Sub-Saharan Africa